2017
DOI: 10.1016/j.nbd.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral administration of the soluble TNF inhibitor XPro1595 modifies brain immune cell profiles, decreases beta-amyloid plaque load, and rescues impaired long-term potentiation in 5xFAD mice

Abstract: Clinical and animal model studies have implicated inflammation and peripheral immune cell responses in the pathophysiology of Alzheimer’s disease (AD). Peripheral immune cells including T cells circulate in the cerebrospinal fluid (CSF) of healthy adults and are found in the brains of AD patients and AD rodent models. Blocking entry of peripheral macrophages into the CNS was reported to increase amyloid burden in an AD mouse model. To assess inflammation in the 5xFAD (Tg) mouse model, we first quantified centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 54 publications
8
91
0
Order By: Relevance
“…8 J, K ). The numbers and proportions of each cell population in blood samples from Ccr2 RFP/ϩ heterozygous animals were similar to previously published materials, suggesting effective detection and discrimination (MacPherson et al, 2017). CCR2-RFP fluorescence was somewhat stronger in Ccr2 RFP/ RFP KO mice (Fig.…”
Section: Flow Cytometry Characterization Of Ccr2 Cellssupporting
confidence: 86%
See 2 more Smart Citations
“…8 J, K ). The numbers and proportions of each cell population in blood samples from Ccr2 RFP/ϩ heterozygous animals were similar to previously published materials, suggesting effective detection and discrimination (MacPherson et al, 2017). CCR2-RFP fluorescence was somewhat stronger in Ccr2 RFP/ RFP KO mice (Fig.…”
Section: Flow Cytometry Characterization Of Ccr2 Cellssupporting
confidence: 86%
“…Cells were suspended in 1ϫ HBSS (Hank's Balance Salt Solution without calcium, Invitrogen), and 1 million cells were stained for flow cytometry. Methods are as previously described in more detail (MacPherson et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, significant differences in slope between treatment groups indicate that XPro1595 treatment dampened inflammation. Systemic dosing of XPro1595 achieved plasma levels of 10-117μg/mL, CSF levels of 3-83 ng/mL, and cortex levels of 1-38 ng/mL in animals that received the drug, while vehicle animals were below detectable levels or below the lowest levels found in XPro1595-treated animals (Figure S5), consistent with previous published studies in rodents (Barnum et al, 2014;MacPherson et al, 2017).…”
Section: Delayed Administration Of Xpro1595 Mitigated Pro-inflammatorsupporting
confidence: 89%
“…Conversely, TNFR2 activation protects against glutamate‐induced excitotoxicity (Marchetti et al , ; Olmos & Llado, ). Moreover, it has been shown that selective inhibition of soluble TNF restores the synaptic dysfunction and long‐term potentiation impairment in 5XFAD mice (MacPherson et al , ). Further research is needed to address these possibilities in our established models.…”
Section: Discussionmentioning
confidence: 99%